2022
DOI: 10.3390/sports10070101
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Age Effect in the Best Track and Field Athletes Aged 10 to 15 Years Old

Abstract: (1) The purpose of this study was to examine the prevalence of the relative age effect (RAE) in the best young (10 to 15 years old) track and field athletes. (2) Hypothesis: The prevalence of the RAE in the best young track and field athletes of both genders will be evident in all age groups from 10 to 15 years old, which may be associated with the significant relationship between biological maturity, chronological age, and the development of physical qualities. (3) Materials and methods: In total, 1778 athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The meaningful swimmer's representation, who were born in the 2nd quartile and the less amount of para swimmers who were born in the 3nd and 4nd quartiles of the year seem to evidence a discrimination against relatively younger children solely because they were born in certain months of the year 11,16,17 and corroborate with previous studies 6,9,18 . In fact, swimming is a sport in which the greatest prevalence of the relative age effects has been observed, with increased participation in championships for those born in the first quartiles 9,10 and a high perceived precocity in elite competition 1 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The meaningful swimmer's representation, who were born in the 2nd quartile and the less amount of para swimmers who were born in the 3nd and 4nd quartiles of the year seem to evidence a discrimination against relatively younger children solely because they were born in certain months of the year 11,16,17 and corroborate with previous studies 6,9,18 . In fact, swimming is a sport in which the greatest prevalence of the relative age effects has been observed, with increased participation in championships for those born in the first quartiles 9,10 and a high perceived precocity in elite competition 1 .…”
Section: Discussionsupporting
confidence: 88%
“…Consequently, this might have implications on the strength demands and the propulsive forces applied 7 . According to Bezuglov et al 11 similar effects are reported in Athletics disciplines, which creates discrimination against late-born and late-maturing children.…”
Section: Introductionmentioning
confidence: 73%
“…The acquisition of technical skills and explosive power that are necessary for these disciplines cannot be attained before the age group of 14-15 years. This is primarily attributed to the significant correlation between biological maturation, chronological age, and the enhancement of physical attributes (Bezuglov et al, 2022), alongside the prolonged instruction required for superior throwing techniques (Kirkeberg et al, 2022). Despite declining age influence in explosive power sports with age, age-related effects persist in senior levels.…”
Section: Figurementioning
confidence: 99%